2011
DOI: 10.1002/jso.23022
|View full text |Cite
|
Sign up to set email alerts
|

Composite biological reconstruction following total calcanectomy of primary calcaneal tumors

Abstract: Therapeutic Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 28 publications
1
36
0
Order By: Relevance
“…The reference treatment is a surgical resection with satisfactory results. However, treatment by conservative surgery is not restricted to removal of the tumor in free margins [2], and the final aim is to restore normal gait. This involves several factors including bearing of weight without deformation of the hindfoot and normal movement of the Achilles tendon and plantar fascia to allow plantigrade locomotion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reference treatment is a surgical resection with satisfactory results. However, treatment by conservative surgery is not restricted to removal of the tumor in free margins [2], and the final aim is to restore normal gait. This involves several factors including bearing of weight without deformation of the hindfoot and normal movement of the Achilles tendon and plantar fascia to allow plantigrade locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…In both reports, osteointegration was successful with satisfactory functional results. However, the authors reported secondary osteonecrosis of the hindfoot at 4-year follow-up in both studies.Li et al [2, 5, 6] recommended the use of composite fibular flaps with or without allograft and achieved satisfactory functional and oncologic results. No information was given on postoperative foot statics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstruction of the hindfoot after partial or total calcanectomy is a challenging procedure in which the goals are reconstruction of the length of the hindfoot to preserve normal tarsal biomechanics and the restoration of reliable soft tissue coverage [16,17]. Due to the infrequency of this condition, there are few cases reporting on limb-salvage procedures with the use of bone allografts, vascularized musculocutaneous flaps, and custom-made prosthesis replacements; most of them with satisfactory functional outcome [8,9,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the infrequency of this condition, there are few cases reporting on limb-salvage procedures with the use of bone allografts, vascularized musculocutaneous flaps, and custom-made prosthesis replacements; most of them with satisfactory functional outcome [8,9,[16][17][18]. In the case of calcanectomy without reconstruction, satisfactory function has also been reported, however cosmetic deformity, ulceration of the skin, and additional deformities frequently occur after such procedure [19,20].…”
Section: Discussionmentioning
confidence: 99%